Perancangan mainan konstruktif untuk membantu tumbuh kembang anak kreatif - Utomo, Deki; Prasetya, Rahmawan Dwi; Jayadi, Nor (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Early age or the golden age is a time of rapid development and growth of children. Education and stimulation through children's play activities are very influential for children's physical and mental development. Play is a need for early childhood that must be met for children's cognitive and motor development. But giving too many toys to children can inhibit children's creativity, make children bored quickly, and make children's concentration decrease. Children aged 5-6 years have the characteristics of more concrete thinking, realism, and high imagination. Based on this background, the author will design a constructive toy for children aged 5-6 years that can increase children's creativity with a more varied game system for children to play to challenge their creativity. The design method used is design thinking with five stages, namely empathise, define, ideate, protoype, and test. This design produces constructive toys for children aged 5-6 years with a flexible connection system adapted to the shape of the joints of motion, with this connection system toys can be arranged and moved so that children can maximally develop their imagination.